Cadaveric aorta implantation for aortic graft infection. (2016) - Ali, Asad; Bahia, Sandeep S.S.; Ali, Tahir
Highlights: Aortic graft infections occur in approximately 0.2–5% of cases of open aortic reconstruction [1–4]. They are associated with significant morbidity and mortality including graft disruption, haemorrhage or sepsis [1–4]. Using a cryopreserved allograft aorta in the treatment of prosthetic graft infection is poorly evidenced. Further studies are required to compare treatments.Patients presenting acutely even years after aortic surgery should be appropriately imaged to rule out graft related problems. Abstract: This case report describes a 73-year-old gentleman who underwent explantation of an infected prosthetic aorto-iliac graft and replacement with a cryopreserved thoracic and aorto-iliac allograft. The patient has been followed up a for more than a year after surgery and remains well. After elective tube graft repair of his abdominal aortic aneurysm (AAA) in 2003, he presented to our unit in 2012 in cardiac arrest as a result of a rupture of the distal graft suture line due to infection. After resuscitation he underwent aorto-bifemoral grafting using a cuff of the original aortic graft proximally. Distally the new graft was anastomosed to his common femoral arteries, with gentamicin beads left in situ. Post discharge the patient was kept under close surveillance with serial investigations including nuclear scanning, however it became apparent that his new graft was infected and that he would require aortic graft replacement, an operation with a mortality of at least 50%. The patient underwent the operation and findings confirmed a synthetic graft infection. This tube graft was explanted and a cryopreserved aorta was used to the refashion the abdominal aorta and its bifurcation. The operation required a return to theatre day one post operatively for a bleeding side branch, which was repaired. The patient went on to make a full recovery stepping down from the intensive therapy unit day 6 post operatively and went on to be discharged 32 days after his cryopreserved aorta implantation.